Adjektiva Denominal dalam Bahasa Jawa - . Sumadi (Humaniora, 2012)
This writing describes the form and the meaning of denominal adjectives in Javanese, especially derivatived through affixation process by applied qualitative-descriptive method. In the Javanese denominal adjectives can be in the form of N-D, mi-D, -um-D, D-an, D-en, and N-D-i. Each formatted denominal adjectives expressed a particular meaning.